Molecular dynamics simulation of thermodynamic and transport properties of H-bonded low-temperature substances - Tychengulova, A.; Aldiyarov, A.; Drobyshev, A. (Физика низких температур, 2015)
The results of modeling of isotopic water mixture clusters in nitrogen and argon cryomatrices are presented. Earlier, our experimental studies of water mixture in cryomatrix have shown that changes in the concentration of analyte in matrix leads to a splitting of the absorption bands characteristic frequencies of the molecules in the IR spectrum. Moreover the multiplicity of characteristic absorption bands in the IR spectrum remained unchanged during heating of the samples from the condensation temperature to the sublimation temperature of the matrix element. In order to find out what structure of clusters is responsible for the immutability of the absorption bands in the vibrational spectrum during thermal cycling of the samples, computer research of water molecules enclosed in nitrogen and argon cryomatrices by the molecular dynamics simulation was conducted. For this purpose, theoretical studies were carried out using computer software packages, that implement used by us semi empirical and ab initio molecular dynamics methods. As a result of the research, the data must be obtained are of theoretical interest for summarizing the physical and chemical properties of systems, consisting of water molecules, and their combination with inert gases for studying the properties of molecular crystals composed of small molecules.